PENGARUH CURRENT RATIO, NET PROFIT MARGIN, DEBT TO EQUITY RATIO, DAN TOTAL ASSET TURNOVER TERHADAP HARGA SAHAM PERUSAHAAN PERTAMBANGAN PERIODE 2018 - 2020 - CATHERINE WIJAYA (Fakultas Ekonomi Prodi Akuntansi, 2022)
The purpose of this study is to determine the effect of Current Ratio, Net Profit Margin, Debt To Equity Ratio, and Total Asset Turnover on Stock Prices in mining sector companies listed on the Indonesia Stock Exchange in 2018 – 2020. This study is a quantitative study. The population of this research is IDX mining sector companies as many as 47 companies. The research sample used purposive sampling method, so the number of samples was 21 companies. The statistical method used is multiple linear regression analysis. The results showed that partially stated Net Profit Margin, Debt To Equity Ratio, and Total Asset Turnover had an effect on stock prices while the Current Ratio had no effect on stock prices. And also simultaneously states the Current Ratio, Net Profit Margin, Debt To Equity Ratio, and Total Asset Turnover affect the Stock Price. The conclusion of this study is that only Net Profit Margin, Debt To Equity Ratio, and Total Asset Turnover have an effect on share prices in mining sector companies listed on the IDX in 2018 - 2020. Keywords: Current Ratio, Net Profit Margin, Debt to Equity Ratio, Total Asset Turnover, Stock Prices